The impact of broadband and other infrastructure on the location of new business establishments - Daire McCoy; Sean Lyons; Edgar Morgenroth; Donal Palcic; Leonie Allen (International Telecommunications Society (ITS), 2016)
Can improving local infrastructure in underdeveloped areas encourage entrepreneurial activity? If so, which infrastructures and by how much? This paper analyses the impact on new business establishments of broadband infrastructure, motorways, airports and railways and a range of other local characteristics such as availability of human capital and access to third level educational facilities. The sample period spans the introduction and recent history of broadband in Ireland, and during this period 86% of the current motorway network was constructed. Human capital, measured as the percentage of the population with a third level qualification and proximity to a third level institution prove to be important determinants of new firm establishments. Availability of broadband infrastructure is significant, but its effects may be mediated by the presence of sufficiently high educational attainment in the area. Transport infrastructure access is significant for some sectors. For all sectoral groupings examined, firm establishments seem to favour a more diverse local sectoral mix rather than a concentrated one.
Keywords: R3; R11; D22; 330; New business establishments; ICT; Infrastructure; Count panel regression model